Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/ijms18030631
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Polyphenol Compounds of Five Muscadine Grapes Cultivated in the United States and in Newly Adapted Locations in China

Abstract: Polyphenol compositions and concentrations in skins and seeds of five muscadine grapes (cv. "Noble", "Alachua", "Carlos", "Fry", and "Granny Val") cultivated in the United States (Tallahassee-Florida, TA-FL) and South China (Nanning-Guangxi, NN-GX and Pu'er-Yunnan, PE-YN) were investigated, using ultra performance liquid chromatography tandem triple quadrupole time-of-flight mass spectrometry (UPLC Triple TOF MS/MS). Fourteen ellagitannins were newly identified in these muscadine grapes. The grapes grown in NN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 35 publications
4
32
1
3
Order By: Relevance
“…() and Wei et al. () for V. rotundifolia Michx grapes. However, variation for specific cultivar still was observed.…”
Section: Resultsmentioning
confidence: 97%
“…() and Wei et al. () for V. rotundifolia Michx grapes. However, variation for specific cultivar still was observed.…”
Section: Resultsmentioning
confidence: 97%
“…“Carlos” flowered approximately one week later, and had one week longer growing season compared with “Noble.” European grapes were collected at three representative stages of berry development: small berries (35 DPB; e.g., “CS,” 24 May 2013 and 5 June 2014), veraison berries (65 DPB, 23 June 2013 and 5 July 2014), and fully ripened berries (85 DPB, 13 July 2013 and 25 July 2014). Grapes were picked randomly from the top, central, and bottom parts of the cluster per target phase, taking into account the balance between shadow and sun exposure, and avoid edge and center effects (Wei et al, ). Samples were immediately transported under refrigeration (ca.…”
Section: Methodsmentioning
confidence: 99%
“…Sample analysis was carried out as previously described (Wei et al, ), using an Eksigent ultraLC 110 and a Triple TOF 4600 (AB SCIEX, Framingham, MA, USA), coupled with a Duospray Ion Source interface and an automatic Calibrant Delivery System. The ultra‐performance liquid chromatography (UPLC) separation was performed on a reversed‐phase Zorbax SB‐C18 column (2.1 mm ×150 mm ×5 μm, Agilent Technologies, Santa Clara, CA, USA) at 35°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that this grape confers multiple health benefits to humans, including cancer inhibition [5,6], a function that is primarily attributed to phenolic compounds [7]. Recently, several varieties of muscadine grapes were introduced to South China, and they adapted well to the climate [8]. One of these varieties, ‘Noble’, is a cultivar used for wine making [9,10].…”
Section: Introductionmentioning
confidence: 99%